2020
DOI: 10.1186/s12943-019-1121-0
|View full text |Cite
|
Sign up to set email alerts
|

Functions and clinical significance of circular RNAs in glioma

Abstract: CircRNAs are a class of single-stranded RNA molecules with a covalently closed loop structure and have been characterized by high stability, abundance, conservation, and display tissue/developmental stage-specific expression, furthermore, based on the abundance in distinct body fluids or exosomes, circRNAs present novel biomarkers and targets for the diagnosis and prognosis of cancers. Recently, the regulatory mechanisms of biogenesis and molecular functions, including miRNAs and RBPs sponge, translation as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(103 citation statements)
references
References 160 publications
1
93
0
1
Order By: Relevance
“…Hence, circRNAs lack a 5′-cap and 3′-polyA tail, which makes them resistant to RNase R treatment. CircRNAs exert their biological functions during cellular processes, including acting as miRNA and protein sponges and modulating parental gene transcription and protein translation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, circRNAs lack a 5′-cap and 3′-polyA tail, which makes them resistant to RNase R treatment. CircRNAs exert their biological functions during cellular processes, including acting as miRNA and protein sponges and modulating parental gene transcription and protein translation [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has recently indicated that there are numerous circRNAs expressed in neuronal tissues, and that dysregulation of circRNAs can lead to diseases of the nervous system, including glioma [35]. The detailed regulatory molecular mechanisms of circRNAs include direct transcription and translation into functional proteins, transcriptional, and splicing regulation as well as miRNAs and RBP sponges [21,27,36].…”
Section: Discussionmentioning
confidence: 99%
“…The findings mentioned above provided an important molecular and theoretical basis for the tissue-and disease-specific expression patterns of circRNAs. Moreover, studies on the correlation between the differential expression of circRNAs and the pathological grade or prognosis of glioma also confirmed the tissue specificity (41,42).…”
Section: Circrna Expression In Gliomasmentioning
confidence: 69%